Farewell Luncheon at Cedar Lanes Bowling Alley for Tomar Mason II - Watkins, Howard::::::::: (1986)
Galen Larson, Tomar's mother, Tomar Mason, her father-William Mason speaking, Justice Pauline Davis Hanson and Referee Phillip Silva